Developments in scan shift power reduction: a survey - Sontakke, Vijay; Dickhoff, John (Institute of Advanced Engineering and Science, 2023)
While power reduction during testing is necessary for today's low-power devices, it also lowers test costs. Scan-based methods are the most widely used approach for testing integrated circuits (IC). Test vectors are shifted into and out of scan chains bit by bit during shift operation. The time required for shift operation dominates the test time. With the geometries shrinking (7 nm→5 nm→3 nm→1.8 nm), ICs are required to be tested for newer defects, increasing test time. The most effective way to reduce test time for scan operation is to increase the frequency of the shift operation. Reduction in shift power enables scan operation to be performed with increased frequency, reducing test time, and test cost. This paper presents a survey of techniques proposed recently for shift power reduction. Various techniques, including special flip-flop usage, segmentation, reordering, and low-pass filter, are being reviewed. The techniques are organized based on main attributes to underscore their similarities and differences. Pros and cons in terms of complexities involved in their implementation are discussed. We believe this paper will provide a point of reference for further studies in scan shift power reduction and will be helpful to both industry and academia.